Adipose-Derived Stem Cells in Radiotherapy Injury: A New Frontier - Shukla, Lipi; Morrison, Wayne A.; Shayan, Ramin (Frontiers in Surgery, 2015)
Radiotherapy is increasingly used to treat numerous human malignancies. In addition to the beneficial anti-cancer effects, there are a series of undesirable effects on normal host tissues surrounding the target tumour. Whilst the early effects of radiotherapy (desquamation, erythema and hair loss) typically resolve, the chronic effects persist as unpredictable and often troublesome sequelae of cancer treatment, long after oncological treatment has been completed. Plastic surgeons are often called upon to treat the problems subsequently arising in irradiated tissues, such as recurrent infection, impaired healing, fibrosis, contracture and/or lymphoedema. Recently, it was anecdotally noted - then validated in more robust animal and human studies - that fat grafting can ameliorate some of these chronic tissue effects. Despite the widespread usage of fat grafting, the mechanism of its action remains poorly understood. This review provides an overview of the current understanding of (i) mechanisms of chronic radiation injury and its clinical manifestations; (ii) biological properties of fat grafts and their key constituent, Adipose-Derived Stem Cells (ADSCs); (iii) the role of ADSCs in radiotherapy-induced soft-tissue injury.